MITIGATING EMERGENCY RISKS IN SUNNAH CUPPING THROUGH MEDICAL AND SHARIA INTEGRATION - Andik Isdianto; Novariza Fitrianti; Abdul Hamid Arif; Wahyudi Widada (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Sunnah cupping therapy is a traditional Islamic health practice increasingly embraced for its spiritual and therapeutic benefits. However, its widespread use, especially by uncertified practitioners, raises serious concerns about patient safety and emergency risks. This study aims to identify key systemic risk factors of medical emergencies related to sunnah cupping and propose an integrative framework combining Islamic jurisprudence (fiqh) with modern clinical standards. A qualitative descriptive approach was employed using a systematic literature review of peer-reviewed journals, clinical reports, Islamic texts, and contemporary fatwas. Thematic analysis revealed five major risk categories: lack of medical screening, unlicensed practitioners, hidden comorbidities, absence of emergency protocols, and poor understanding of medical safety. Reported complications included hypovolemic shock, infections, and prolonged wound healing—especially in patients with undiagnosed diabetes or coagulation disorders. The study also found that public misconceptions equating religious merit with clinical safety further worsen these risks. The research highlights the urgent need for standardized medical and sharia-based training, certification systems, and public education. Collaboration among healthcare professionals, Islamic scholars, and educational institutions is essential to establish a safe, accountable, and spiritually valid model of sunnah cupping. Integrating medical protocols with fiqh compliance can significantly reduce emergency incidents, enhance practitioner competency, and preserve the prophetic nature of the practice within a modern health framework. These findings offer a strategic path for safer implementation of prophetic medicine across Muslim communities.